SURGICAL BREAST CLIPPING FOR DELIMITATION OF RADIOTHERAPY DOSE IN BREAST CANCER - Mendes, Jailson Rodrigues; Silva, Diego de Carvalho; Fé, Taíla Sousa de Moura; Neto, Antônio Marques de Medeiros; Eulálio Filho, Walberto Monteiro Neiva; Vieira, Sabas Carlos (Mastology, 2018)
Objective: To evaluate the benefit of radiotherapy planning, involving the use of surgical clips in conservative treatment of earlystage breast cancer. Methods: Retrospective cohort. Twelve (12) breast cancer female patients were retrospectively evaluated. These women had undergone breast-conserving treatment in which the tumor bed had been demarcated with titanium 200 surgical clips to guide breast boost radiotherapy. Volumes were calculated. Radiotherapy planning in the same patient with boost dose guided by metal clips was compared to planning guided by surgical scar or by imaging tests prior to surgical treatment. Results: A reduction of 36.7% in total volume of the irradiated breast (p=0.022), a reduction of 55.7% in boost volume (p=0.001), a reduction of 35.9% (p=0.001) in the breast volume receiving the prescribed boost dose and a reduction of 4.5% (p=0.014) in the maximum dose applied to the lung were shown. Conclusions: Clip placement in surgical bed following conservative treatment for breast cancer determined a reduction of 36.7% in irradiated breast volume and use of a lower dose of irradiation.